2018
DOI: 10.1111/imj.13716
|View full text |Cite
|
Sign up to set email alerts
|

Chronic myeloid leukaemia and tyrosine kinase inhibitor therapy: assessment and management of cardiovascular risk factors

Abstract: Several BCR-ABL1 tyrosine kinase inhibitors (TKIs) are approved for the first-line treatment of chronic phase chronic myeloid leukaemia (CML). Disease control is achieved in the vast majority of patients and disease-specific survival is excellent. Consequently, there is now emphasis on managing comorbidities and minimising treatment-related toxicity. Second-generation TKIs have cardiovascular risks that are greater than with imatinib treatment, but these risks must be balanced against the superior CML response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
0
20
0
1
Order By: Relevance
“…Notably, the diagnosis was suggested only by echocardiogram in 5 of the 9 patients with this finding; catheterization was only performed (and confirmed the diagnosis) in 4 patients. The overall frequencies of vascular 5,[11][12][13][14][15][16][17][18]37 and cardiac [19][20][21][22][23][24][25][26] AEs varied across various clinical trials depending on the study design, type of TKI, treatment durations, AE definitions, and eligibility criteria. Contrary to some reports, 38 we observed that dasatinib was associated with a higher risk of AT-AE relative to imatinib, with a risk that appears similar to that with nilotinib.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the diagnosis was suggested only by echocardiogram in 5 of the 9 patients with this finding; catheterization was only performed (and confirmed the diagnosis) in 4 patients. The overall frequencies of vascular 5,[11][12][13][14][15][16][17][18]37 and cardiac [19][20][21][22][23][24][25][26] AEs varied across various clinical trials depending on the study design, type of TKI, treatment durations, AE definitions, and eligibility criteria. Contrary to some reports, 38 we observed that dasatinib was associated with a higher risk of AT-AE relative to imatinib, with a risk that appears similar to that with nilotinib.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have sought to define risk factors for VAE development during nilotinib treatment, with a key commonality being the high incidence of at least 1 preexisting cardiovascular risk factor in patients who experience VAEs. 9 Strategies to predict the overall likelihood of VAEs have been proposed 1,17,18 and have formed the basis of recommendations for pre-TKI risk assessment and the avoidance of nilotinib where possible in those at higher risk. 2,9 In addition, regular monitoring for risk factors throughout treatment is recommended, with some authors suggesting a role for angiologic testing such as ankle-brachial index assessment 2,19 and computed tomography coronary calcium scores.…”
Section: Months After First Vaementioning
confidence: 99%
“…9 Strategies to predict the overall likelihood of VAEs have been proposed 1,17,18 and have formed the basis of recommendations for pre-TKI risk assessment and the avoidance of nilotinib where possible in those at higher risk. 2,9 In addition, regular monitoring for risk factors throughout treatment is recommended, with some authors suggesting a role for angiologic testing such as ankle-brachial index assessment 2,19 and computed tomography coronary calcium scores. 9 In line with previous findings, we demonstrated that VAEs were more common in older patients 20 and in those with preexisting cardiovascular risk factors.…”
Section: Months After First Vaementioning
confidence: 99%
See 2 more Smart Citations